MANAGEMENT OF FEDERALLY ALLOCATED REVENUE AND THE DEVELOPMENT OF NIGERIAN ECONOMY - Falmata Baba Abba; Umar Alhaji Umar (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2024)
The aim of Islamic regulation is not limited to the success in the hereafter alone; it also involves the success in the material world. The search for al-Falāḥ is, thus, multi-dimensional, not forgetting the spiritual or belittling the mundane. Revelation, therefore, serves as a guide for human reasoning in search of worldly success and stability. Nigeria has experimented many secular based ideologies and development plans which did not produce into the desired results. From 1962 to date Nigeria has formulated at least seven development plans. This paper suggests the application of the Islamic economic principles which is core to ensure the reduction of poverty, unemployment and creation of a just and egalitarian society, in which growth and development in spiritual and material realms is accomplished.